2017
DOI: 10.2169/internalmedicine.8735-16
|View full text |Cite
|
Sign up to set email alerts
|

Familial Adenomatous Polyposis with Multiple <i>Helicobacter</i>-negative Early Gastric Cancers Treated by Endoscopic Submucosal Dissection

Abstract: Stomach cancer rarely develops in patients with familial adenomatous polyposis (FAP), and Helicobacter pylori infection may increase the risk of FAP-related gastric cancer. We describe the case of a 64-year-old woman who developed multiple synchronous early gastric cancers without H. pylori infection. Nine cancer lesions were successfully treated by endoscopic submucosal dissection. An immunohistochemical analysis revealed that the tumors were positive for mucin (MUC)2, MUC6, and CDX2, but negative for MUC5AC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A case report on gastric cancers in a Japanese FAP patient showed that the tumors were of the gastrointestinal type (Yaguchi et al, 2017). Another case report showed that an FAP patient had a gastric-type adenocarcinoma whereas his pedigree had an intestinal-type adenocarcinoma (Mitsui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case report on gastric cancers in a Japanese FAP patient showed that the tumors were of the gastrointestinal type (Yaguchi et al, 2017). Another case report showed that an FAP patient had a gastric-type adenocarcinoma whereas his pedigree had an intestinal-type adenocarcinoma (Mitsui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…MUC2, CDX2, and CD10 are also useful immunohistochemical markers that can be used to subclassify gastric cancers into the gastric, intestinal, and mixed gastrointestinal types (Mitsui et al., 2019). A case report on gastric cancers in a Japanese FAP patient showed that the tumors were of the gastrointestinal type (Yaguchi et al., 2017). Another case report showed that an FAP patient had a gastric‐type adenocarcinoma whereas his pedigree had an intestinal‐type adenocarcinoma (Mitsui et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Japan have indicated that the prevalence rate of gastric cancer in patients with FAP was 3.1–4.2% [ 49 , 60 ], but studies in Western countries indicated that the prevalence rate was low at 0.6% [ 46 ]. Studies in Japan on gastric cancer in patients with FAP are more diverse than the general population, including gastric cancer caused by fundic gland polyposis, gastric cancer caused by gastric mucosal atrophy due to H. Pylori infection, and coexistence high-grade adenoma/ dysplasia [ 44 , 133 , 134 ], and there are many cases of early detection with periodic endoscopic surveillance [ 130 , 133 , 134 ]. Meanwhile, gastric cancers that develop in GAPPS, which is a polyposis limited to the stomach due to pathogenic germline variants in the promoter 1B of the APC gene, require differentiation at the time of initial diagnosis due to its high malignancy [ 135 ].…”
Section: Commentsmentioning
confidence: 99%